2019
DOI: 10.9734/ajfar/2019/v4i430060
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Flesh Quality of Clarias gariepinus in Farm-raised and Wild Populations

Abstract: Aim. Nutrients analysis of wild and farmed raised African catfish (Clarias gariepinus, Burchell, 1822) were studied. The comparative work was carried out to find out if habitat could affect the nutrient composition of the fish. Study design: Five live C. gariepinus were obtained for three wild location and three fish farm each (n=30). One-way analysis of variance was use to examine the nutrients composition across the study locations. Methodology: Five individual fishes were randomly selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The pond-cultured fish species had significantly (p<0.05) higher moisture contents than the wild fish species leading to the wild fish species having higher concentrations of nutrients. Similar results for cultured and wild C. gariepinus collected respectively from Ondo State in Nigeria reported that the moisture content was significantly higher (p < 0.05) in the cultured C. gariepinus (6.24 ± 0.10%) than wild C. gariepinus (5.43 ± 0.11%) [26]. The findings also revealed that O. niloticus contains significantly higher moisture levels than C. gariepinus which is consistent with the findings of a previous study on the species where the values were lower than in the current study [27].…”
Section: Proximate Compositionsupporting
confidence: 72%
“…The pond-cultured fish species had significantly (p<0.05) higher moisture contents than the wild fish species leading to the wild fish species having higher concentrations of nutrients. Similar results for cultured and wild C. gariepinus collected respectively from Ondo State in Nigeria reported that the moisture content was significantly higher (p < 0.05) in the cultured C. gariepinus (6.24 ± 0.10%) than wild C. gariepinus (5.43 ± 0.11%) [26]. The findings also revealed that O. niloticus contains significantly higher moisture levels than C. gariepinus which is consistent with the findings of a previous study on the species where the values were lower than in the current study [27].…”
Section: Proximate Compositionsupporting
confidence: 72%